CDK2 and PKA Mediated-Sequential Phosphorylation Is Critical for p19INK4d Function in the DNA Damage Response - Marazita, Mariela C.; Ogara, M. Florencia; Sonzogni, Silvina V.; Martí, Marcelo; Dusetti, Nelson J.; Pignataro, Omar P.; Cánepa, Eduardo T. (PLOS ONE, 2012)
DNA damage triggers a phosphorylation-based signaling cascade known as the DNA damage response. p19INK4d, a member of the INK4 family of CDK4/6 inhibitors, has been reported to participate in the DNA damage response promoting DNA repair and cell survival. Here, we provide mechanistic insight into the activation mechanism of p19INK4d linked to the response to DNA damage. Results showed that p19INK4d becomes phosphorylated following UV radiation, β-amyloid peptide and cisplatin treatments. ATM-Chk2/ATR-Chk1 signaling pathways were found to be differentially involved in p19INK4d phosphorylation depending on the type of DNA damage. Two sequential phosphorylation events at serine 76 and threonine 141 were identified using p19INK4d single-point mutants in metabolic labeling assays with 32P-orthophosphate. CDK2 and PKA were found to participate in p19INK4d phosphorylation process and that they would mediate serine 76 and threonine 141 modifications respectively. Nuclear translocation of p19INK4d induced by DNA damage was shown to be dependent on serine 76 phosphorylation. Most importantly, both phosphorylation sites were found to be crucial for p19INK4d function in DNA repair and cell survival. In contrast, serine 76 and threonine 141 were dispensable for CDK4/6 inhibition highlighting the independence of p19INK4d functions, in agreement with our previous findings. These results constitute the first description of the activation mechanism of p19INK4d in response to genotoxic stress and demonstrate the functional relevance of this activation following DNA damage.